Sexuality, HIV and Drug use among University Students - Ajulo M.O., Ajulo H.O. (Journal of Applied Pharmaceutical Science)
Sexuality, HIV prevalence and drug used among students of University of Uyo were investigated through a survey that involved use of questionnaires and analysis of blood specimens. The study involved use of questionnaire and collection of blood samples from sampled students. Informed consent forms were given out to students to read and those who met the criteria were allowed to participate in the study. The result of the study indicated that fiftyseven (58.1%) of the students have sexual intercourse. Sixty-eight (69.39%) students have sexual intercourse with one sex- partners while seven (7.14%) students have multiple sexpartners. Fifty-two (91.23%) students use condom during sexual activity while five (8.77%) had sexual intercourse without using condom. Rate of sexual activity demonstrated among the volunteered students follows this trend; abstinence (22.45%), once weekly (17.35%), twice weekly (5.10%), and once daily (4.08%) respectively. The study further revealed that eightyfive (86.7%) students know their HIV status while forty (70.18%) know the HIV status of their sex- partners. In spite of the current campaign on HIV, there are students who lack adequate knowledge of HIV transmission and prevention leading to unprotected sexual intercourse.
Keywords: HIV, life challenges, sex-partner, sexuality, sexual activity.